Anonymous
Topics: Science
f'(x) = x^(3/2), so f'(4) = 4^(3 / 2) = 8.
Replace the x's with g (sqrt(3)), so f(g)=sqrt(3)*U3+2. !
I'm sorry I could not find the answer you are looking for. !
To solve f(x)=x-11 for f(4), you simply plug 4 into the equation every time x...
These hyperbolas are shifted 4 to the left and compressed by 1/4. !
x = 1, -4, -3
Google is -paying 97$ per hour!...
CHACHA IS NOW OUT OF BUSINESS-
Dante, Dominic Zamprogna, from General Hospital once told Soap Opera Digest that...
No, all of Santa's weight gain in The Santa Clause was either a fat suit or...
No, Tim Allen did not gain weight for the movie The Santa Clause, it was a fat...